HYDRULIC TRAFFIC REDUCE SYSTEM - D. M. Inamdar; Sushantkumar B. Bhagat; Vijay B. Burungale; Rushikesh B. Ghadage; Joshi Prasad D. (International Journal of Innovations in Engineering Research and Technology, 2022)
One of the primary challenges has been traffic congestion. India is one of the world's quickest and largest economies. Because India has such a large population, there are a large number of private vehicles on the road, causing traffic congestion. As a result, we've introduced the new way to address this issue. In the event of an emergency, on the roadside if there is heavy traffic and an emergency vehicle needs to pass. We can allow the vertical movement of the footpath so that cars can simply crawl on to it and clear their way by employing a hydraulic traffic reduction system, which uses a hydraulic mechanism beneath the sidewalk. By incorporating this system into the construction of the new road, we will be able to save money while also assisting in times of need. As a result, we can reduce traffic congestion during inclement weather and emergencies.